Production of Biodiesel Using Tannery Fleshing as a Feedstock: An Investigation of Feedstock Pre-Treatment Via Solid-State Fermentation - Santhana, Krishnan; Zularisam, A. W.; Singh, Lakhveer; Mimi Sakinah, A. M. (Asian Research Publishing Network (ARPN), 2016)
Depleting fossil fuel resources, increasing cost and the effect of GHGs has signalled the exploration alternative fuels for diesel engines. This study focused on transesterification using tannery fleshing as a feedstock and sodium hydroxide as a homogenous catalyst. The tannery fleshing was pre-treated via solid-state fermentation in order to reduce the free fatty acids present in it. The optimum conditions for the transesterification were: time 3 h; methanol to oil ratio 6:1 and catalyst amount 1% with highest methyl ester content at 89 wt. %.